2009
DOI: 10.1074/jbc.m109.023994
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeranyl Pyrophosphate Is a Potent Regulator of HRD-dependent 3-Hydroxy-3-methylglutaryl-CoA Reductase Degradation in Yeast

Abstract: 3-Hydroxy-3-methylglutaryl (HMG)-CoA reductase (HMGR), the rate-limiting enzymes of sterol synthesis, undergoes feedback-regulated endoplasmic reticulum degradation in both mammals and yeast. The yeast Hmg2p isozyme is subject to ubiquitin-mediated endoplasmic reticulum degradation by the HRD pathway. We had previously shown that alterations in cellular levels of the 15-carbon sterol pathway intermediate farnesyl pyrophosphate (FPP) cause increased Hmg2p ubiquitination and degradation. We now present evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
84
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 28 publications
8
84
2
Order By: Relevance
“…Interestingly, in a recent study Garza et al (59) have demonstrated that degradation of Hmg2p in Saccharomyces cerevisiae is stimulated by GGPP rather than GGOH, and that GGPP is involved in Hmg2p ubiquitylation but not dislocation. However, in the yeast, prevention of protein geranylgeranylation did not hamper the effect of GGPP, indicating that prenylated protein(s) is(are) not involved in Hmg2p turnover (59). Although these results appear to contrast the data presented here, it should be emphasized that Hmg2p stability in yeast is controlled mainly by FPP-derived nonsterol (GGPP) rather than by sterols (59,60).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Interestingly, in a recent study Garza et al (59) have demonstrated that degradation of Hmg2p in Saccharomyces cerevisiae is stimulated by GGPP rather than GGOH, and that GGPP is involved in Hmg2p ubiquitylation but not dislocation. However, in the yeast, prevention of protein geranylgeranylation did not hamper the effect of GGPP, indicating that prenylated protein(s) is(are) not involved in Hmg2p turnover (59). Although these results appear to contrast the data presented here, it should be emphasized that Hmg2p stability in yeast is controlled mainly by FPP-derived nonsterol (GGPP) rather than by sterols (59,60).…”
Section: Discussioncontrasting
confidence: 56%
“…However, in the yeast, prevention of protein geranylgeranylation did not hamper the effect of GGPP, indicating that prenylated protein(s) is(are) not involved in Hmg2p turnover (59). Although these results appear to contrast the data presented here, it should be emphasized that Hmg2p stability in yeast is controlled mainly by FPP-derived nonsterol (GGPP) rather than by sterols (59,60). Thus, unlike the mammalian reductase, degradation of Hmg2p in yeast does not involve co-signaling by different MVA-derived metabolites, and GGPP may fulfill all the requirements as a metabolic degradation signal.…”
Section: Discussioncontrasting
confidence: 56%
“…Our more recent work has shown that geranylgeranyl pyrophosphate (GGPP), which is structurally analogous to FPP but with 20 carbons, is the likely bona fide signal (see Fig. 1) (22). In addition, we have shown that an oxysterol signal appears to modulate the degradation of Hmg2 as well; increased levels of certain oxysterols enhance the degradation rate controlled by endogenous levels of the FPP-derived signal (23).…”
mentioning
confidence: 83%
“…22. Following treatment with drugs or control treatment, the fluorescence of 10,000 cells in each sample was measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation